New horizons in the treatment of psoriasis: Modulation of gut microbiome - Mojtaba Memariani; Hamed Memariani (Heliyon)
The last decennia have witnessed spectacular advances in our knowledge about the influence of the gut microbiome on the development of a wide swathe of diseases that extend beyond the digestive tract, including skin diseases like psoriasis, atopic dermatitis, acne vulgaris, rosacea, alopecia areata, and hidradenitis suppurativa. The novel concept of the gut-skin axis delves into how skin diseases and the microbiome interact through inflammatory mediators, metabolites, and the intestinal barrier. Elucidating the effects of the gut microbiome on skin health could provide new opportunities for developing innovative treatments for dermatological diseases. Psoriasis is a complex disease with multiple factors contributing to its development, such as diet, lifestyle, genetic predisposition, and the microbiome. This paper has a dual purpose. First, we outline the current knowledge on the unique gut microbiota patterns implicated in the pathogenesis of psoriasis. Second, and of equal importance, we briefly discuss the reciprocal impact of psoriasis treatment and gut microbiome. In addition, this review explores potential therapeutic targets based on microbial interventions, which hold promise for providing new treatment options for psoriasis.